Achieving Power System Stability for Two Area Hydro Power System via LQR Techniques - Shaharudin, Nabilah; Nizam Kamarudin, Muhammad; Hendra Hairi, Mohd; Ismael Rizman, Zairi (International Journal of Engineering and Technology, 2018)
Maintaining synchronism between different parts of power system is getting difficult over time. Frequency perturbation in power system can cause stalling in loads. If synchronism between generator and the power systems is lost at any time, voltage and current fluctuations may happen that gives catastrophic effect to the end users and power systems. In this paper, two area hydropower system was represented in state space form. The controllability and observability of the system were tested. The frequency deviation observer for both areas was formulated. Hence, the state feedback via integration of Linear Quadratic Regulator (LQR) and PI controller was designed for load frequency control (LFC) to preserve the stability of the power system due to load frequency deviation. The performance and efficacy of the proposed controller were then compared with traditional Proportional-Integral (PI) controller. The effectiveness of the proposed controller approach was demonstrated through two area hydropower system using MATLAB with SIMULINK toolbox.Â Â